Hybridisation on coral reefs and the conservation of evolutionary novelty - Richards, Zoe; Hobbs, Jean-Paul (Zhongguo Kexueyuan Dongwu Yanjiusuo,Chinese Academy of Sciences, Institute of Zoology, 2015)
Hybridisation was traditionally considered rare on coral reefs. However, a rapid increase in hybrid studies over the last 20 years has revealed that hybridisation on coral reefs is common and widespread. In this review, we summarise the growing body of evidence arising from studies on stony corals and reef fishes to verify the occurrence of hybridisation, and we examine the influence hybridisation has had on the enormous level of biodiversity present on coral reefs. We discuss the challenges of distinguishing hybridisation from alternative hypotheses (e.g. incomplete lineage sorting). This review also explores the evolutionary consequences of hybridisation, which range from increasing genetic diversity and the production of novel lineages that may outperform the parent species, to reverse speciation and extinction by genetic swamping. Instances of hybridisation can be natural or occur as a result of human impacts (e.g. habitat degradation) and distinguishing between these two very different causal mechanisms is important for management. Currently, the legislative status of hybrids is unclear and hybrids are rarely protected in conservation programs. Failing to adequately manage hybridisation and hybrid lineages may lead to potential losses of evolutionary novelty, declines in phylogenetic diversity or species extinctions. To conserve existing coral reef biodiversity, and the processes that generate biodiversity, conservation policies must be re-defined and instances of hybridisation must be assessed and managed on a case-by-case basis.